(untitled) (Altre Modernità, 2016)
The demands raised by the Chilean university students during the social movements occurred during the year 2011 and its relation to the economic, performance and governance characteristics of Chilean Higher Education are identified and analyzed. The relationship of these demands with your social legitimation is analyzed. The role of these demands is also established as a catalyst for the breakdown of the public confidence in the economic model of Higher Education The political, social and intellectual consequences of these student movements are described in their present state of development, as well as its possible projections.